Gold nanoparticles attenuate metastasis by tumor vasculature normalization and epithelial–mesenchymal transition inhibition - Li W (Dove Medical Press, 2017)
Wei Li,1 Xin Li,1 Shuhao Liu,1 Wende Yang,1 Fan Pan,1 Xiao-Yan Yang,1,2 Bin Du,3 Li Qin,4 Yunlong Pan1 1Department of General Surgery, The First Affiliated Hospital of Jinan University, 2Key Laboratory of Functional Protein Research of Guangdong Higher Education Institutes, Institute of Life and Health Engineering, College of Life Science and Technology, Jinan University, 3Department of Pathology, The First Affiliated Hospital of Jinan University, 4Department of Histology, and Embryology, Medical School of Jinan University, Guangzhou, People’s Republic of China Abstract: Angiogenesis is a process by which vessels are formed through preexisting ones, and this plays a key role in the progression of solid tumors. However, tumor vessels are influenced by excessive pro-angiogenic factors, resulting in deformed structures that facilitate the intravasation of tumor cells into the circulation and subsequent metastasis. Moreover, abnormal tumor vessels have low blood perfusion and thereby decreased oxygen infusion into tumors. This results in a hostile microenvironment that promotes epithelial–mesenchymal transition (EMT), a process in which epithelial cells lose their polarity and gain increased motility, which is associated with metastasis and invasion. Here, we demonstrate that gold nanoparticles (AuNPs) facilitate tumor vasculature normalization, increase blood perfusion and alleviate hypoxia in melanoma tumors. Additionally, AuNPs were observed to reverse EMT in tumors, accompanied by the alleviation of lung metastasis. These AuNPs inhibited the migration of B16F10 cells and reversed EMT in B16F10 cells, indicating that AuNPs could directly regulate EMT independent of improvements in hypoxia. Taken together, our data demonstrated that AuNPs could induce tumor vasculature normalization and reverse EMT, resulting in decreased melanoma tumor metastasis. Keywords: gold nanoparticles, tumor vasculature normalization, tumor metastasis, epithelial–mesenchymal transition